Transabdominal bowel sonography for the detection of intestinal complications in Crohn's disease. Issue 1 (1st January 1999) - Gasche, C; Moser, G; Turetschek, K; Schober, E; Moeschl, P; Oberhuber, G
Abstract : Background: The course of Crohn's disease is characterised by the occurrence of intestinal complications such as strictures, intra-abdominal fistulas, or abscesses. Standard diagnostic procedures may fail to show these complications, in particular fistulas. Aims: To test the value of transabdominal bowel sonography (TABS) for the detection of intestinal complications in Crohn's disease. Methods: TABS was prospectively performed in 213 patients with Crohn's disease in a university based inflammatory bowel disease referral centre. Thirty three underwent resective bowel surgery and were included in this study. The accuracy of TABS to detect strictures, intra-abdominal fistulas, or abscesses was compared with surgical and pathological findings. Results: TABS was able to identify strictures in 22/22 patients and to exclude it in 10/11 patients (100% sensitivity, 91% specificity). Fistulas were correctly identified in 20/23 patients and excluded in 9/10 patients (87% sensitivity, 90% specificity). Intra-abdominal abscesses were correctly detected in 9/9 patients and excluded in 22/24 patients (100% sensitivity, 92% specificity). Conclusions: In experienced hands TABS is an accurate method for the detection of intestinal complications in Crohn's disease. TABS is thus recommended as a primary investigative method for evaluation of severe Crohn's disease.